The Difference in District Leader Self-Efficacy Between Single-Frame and Multiframe Leadership of the Superintendent - Doennig, Martha Bailey (Southwest Baptist University, 2019)
When district leaders lead with a multiframe approach in times of change, a more comprehensive approach is taken to view the organization through a structural, political, symbolic, and human resource lens. In addition, when district leaders hold high levels of self-efficacy, the belief that a difference can be made increases. Therefore, ensuring superintendent leadership that positively influences self-efficacy of the followers is critical to the achievement of effective change There has been little research conducted to understand the single- or multi framing of a superintendent in times of change on the difference of self-efficacy of the district leaders reporting directly to the superintendent. This causal comparative study utilized inferential and descriptive statistics to understand the difference of self-efficacy of district leaders reporting directly to single- and multiframed superintendents in times of change across the state of Missouri. Results from this study showed no statistically significant difference occurred in self-efficacy of district leaders reporting directly to a single- or multiframed superintendent in times of change.